BOREAS SERM Forest Cover Data Layers of the SSA in Vector Format - GRUSZKA, F. (ORNL Distributed Active Archive Center, 2000)
The forest cover data provided by Saskatchewan Environment and Resource Management, Forestry Branch - Inventory Unit (SERM-FBIU) are basically a digital version of its 1:12,500 scale forest cover polygon maps. The data include information on forest parameters and cover the area in and near the BOREAS SSA, excluding the PANP. As a digital archive, however, changes within forest stands can be updated more readily. At the same time, it should be kept in mind that most of these digital forest cover data were acquired in 1993, and the data set has been static since that time.